Information and Market Power in DeFi Intermediation - Azar, Pablo D.,Casillas, Adrian,Farboodi, Maryam (National Bureau of Economic Research, 2024)
This paper considers the
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Finanzintermediation; Blockchain; Elektronisches Handelssystem; Asymmetrische Information; Vertragstheorie; Decentralized Finance; Ethereum; Survey Methods; Sampling Methods; Asymmetric and Private Information; Mechanism Design; Economics of Contract: Theory; Non-bank Financial Institutions; Financial Instruments; Institutional Investors; Other; Information and Internet Services; Computer Software